PERDEBATAN EPISTEMOLOGIS ILMU EKONOMI ISLAM DAN FIQH MUAMALAT - Hadi, Abdul (Nurani, 2013)
Abstract: Islamic Economics is basically a combination of two types of science is the science of economics and the science of religion (fiqh mu'amalat). As like other sciences, Islamic economics also has two formal object of study, namely objects and material objects. Formal object of Islamic economics is the whole system of production and distribution of goods and services by businesses better predictions about aspects of income that will be generated as well as on the legal aspects of a transaction. While the material is all science objects associated with Islamic economics.ملخص: الاقتصاد الإسلامي هو في الأساس مزيج من نوعين من العلم هو علم الاقتصاد وعلوم الدين (فقه المعاملات). ومثل غيره من العلوم، الاقتصاد الإسلامي أيضا اثنين من وجوه رسمية من الدراسة، وهي الكائنات والأشياء المادية. كائن رسمي من الاقتصاد الإسلامي هو النظام برمته من إنتاج وتوزيع السلع والخدمات من قبل الشركات التنبؤات على نحو أفضل عن جوانب الدخل التي سيتم إنشاؤها وكذلك على الجوانب القانونية للمعاملة. في حين أن المادة هي كل الكائنات العلوم المرتبطة الاقتصاد الإسلاميKata Kunci: ilmu ekonomi, fiqh muamalat.